Social housing and the real estate market: agents and dynamics of the Minha casa Minha vida program in Pelotas (Brazil) - Soares Sa Britto, Natalia Daniela [UNESP]; Sobarzo Mino, Oscar Alfredo (Pontifica Univ Catolica Chile, Inst Geografia, 2021)
In this article, housing production in the Brazilian city of Pelotas is analyzed, within the Minha Casa Minha Vida Program (MCMV), between 2009 and 2016. The analyses begin by placing the program's creation in the political-economic context of the first decade of the 21st century, characterized by a resurgence of the state's regulatory and auxiliary role in the process of capital accumulation. The general characteristics of the MCMV are addressed and their impact on the city is analyzed according to the main housing production modalities for different income groups. The article shows that the action of different agents, establishing partnerships when necessary, and the dynamics of housing production, generated an expansion of the urbanized area, with significant peripheral expansion, and the increase in land values and in the value of firms themselves, due to the financialization, without, however, addressing the housing deficit.
Keywords: Social housing; Minha Casa Minha Vida Program; Real estate Market; Land values; Peripheral expansion